Pendekatan Interdisipliner dan Multidisipliner Dalam Studi Islam - Rohmatika, Ratu Vina (Universitas Islam Negeri Raden Intan Lampung, 2019)
This article focuses on the study of the importance of interdisciplinary and multidisciplinary approaches in the study of Islamic science. From the results of the study concluded that the interdisciplinary and multidisciplinary approach is very important in Islamic studies for several reasons: First, the interdisciplinary approach is a very important approach to be encouraged especially if this approach is used to understand the Islamic messages contained in the Qur'an and al-Hadith. Second, the interdisciplinary approach is a new approach to contextualizing Islamic messages, so that the Islamic messages are truly shalih li kulli zaman wa al-makan.